Islamic Education in the Obstruction of Religious Radicalism (Reflection on Epistemology-Methodology) - Muhajir Muhajir (AJIS: Academic Journal of Islamic Studies, 2017)
The change of living pattern into permissive, open, highly-mobile life style, as well as the high risk of anarchistic actions, requires the establishment of steady education system which is capable ofresponding the demanding challenge. Islamic education in particular, is forced to constantly adapt to the existing phenomena arising in society. Based on this consideration, Islamic education curriculum has found its moment to be carefully redesigned as an inclusive, down to earth curriculum promoted as a picture of peaceful tolerant Islam, endlessly sholih li kullizamanwamakan.